Benthic macroalgae of an unpolluted tropical river (Rio Savegre, Costa Rica) - Silva-Benavides, Ana Margarita (1998)
A survey of the benthic macroalgae and physical data was monthly performed in Rio Savegre from its headwaters to its lowplain course. The macroalgae were observed with a viewing box at 20 cm intervals following a fixed rope across the stream and microscopical observations were made at laboratory. The species composition of benthic macroalgae found in Rio Savegre is characteristic for unpolluted. clear. carbonate poor streams. From the source to the mouth a change from species adapted to cold. fast flowing streams to species adjusted to higher temperatures. lower current velocity and periodic desiccation was observed. There was a replacement of the multilayered. well structured macroalgal community in the upper part of the river by surface films formed by microalgae in the lower part. In addition a high-light community consisting of Spirogyro sp., Nostoc verrucosum and Tetraspora sp. could be distinguished from the dim-light species Prosiola mexicana and Hildenbrandia sp.